If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 22 + -7x = 14 Reorder the terms: 22 + 5x + -7x = 14 Combine like terms: 5x + -7x = -2x 22 + -2x = 14 Solving 22 + -2x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + -2x = 14 + -22 Combine like terms: 22 + -22 = 0 0 + -2x = 14 + -22 -2x = 14 + -22 Combine like terms: 14 + -22 = -8 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
| p^2-2p-26=0 | | 5x+2y-(6x+3y)= | | 2cos(6x)=0 | | 4(3x-2)=26 | | Mn*4mn= | | 3w+3x+12y+3w+x-5y= | | x^2-20x+28=0 | | (2sin^2x)-(3cosx)=0 | | X*0.85=12.87 | | ln(x+3)-2ln(x-3)=0 | | 3x^2/2x-5=0 | | 4x-5=2(x-2) | | 2x=42/15 | | 0.2x+x=85 | | (1-2lnx)/x^3=0 | | 6c^6b^9/60c^6b^7 | | x^4-2x^3+7x^2-4x+10=0 | | 2^2x/3=1/16 | | 7x/14y | | (2c)+(C^2)=35 | | 2/n=8/20 | | (c^2)+(2c)=35 | | lnx^2=x | | 2*lnx^2=x | | 11(p-2)=8p+9+3zp | | 2x*lnx=x | | 8y-6=2(4y-3) | | F(x)=2x^4+cos^2x-3 | | 3w^2+24w+21=0 | | ((-8)/3)*((-14)-(-2)) | | 5*-8-16=3(2*-8-3)+1 | | L-9=5(5l-3) |